Features of the Course and Treatment of Obstructive Bronchitis in Early Childhood - Ibragimova Yulduz Batirovna (Journal of Science in Medicine and Life, 2025)
Obstructive bronchitis - a spasm of the bronchi or blockage of the mucous membrane - occurs more often in children than in adults. This is explained by the peculiarities of the anatomical structure, the immaturity of the immune system, and the beginning of active socialization.